Targeting SREBP-1-Mediated Lipogenesis as Potential Strategies for Cancer - Zhao, Qiushi; Lin, Xingyu; Wang, Guan (Frontiers in Oncology, 2022)
Sterol regulatory element binding protein-1 (SREBP-1), a transcription factor with basic helix-loop-helix leucine zipper has two isoforms, SREBP-1a and SREBP-1c derived from the same gene for regulating the genes of lipogenesis, including acetyl-CoA carboxylase, fatty acid synthase, and stearoyl-CoA desaturase. Importantly, SREBP-1 participates in metabolic reprogramming of various cancers, and has been a biomarker for the prognosis or drug efficacy for the patients with cancer. In this review, we first introduced the structure, activation, and key upstream signaling pathway of SREBP-1. Then, the potential targets and molecular mechanisms of SREBP-1-regulated lipogenesis in various types of cancer, such as colorectal, prostate, breast, and hepatocellular cancer were summarized. We also discussed potential therapies targeting SREBP-1-regulated pathway by small molecules, natural products, or the extracts of herbs against tumor progression. This review could provide new insights in understanding advanced findings about SREBP-1-mediated lipogenesis in cancer and its potential as a target for cancer therapeutics.